The effect of dysmenorrhea severity and interference on reactions to experimentally-induced pain - Rogers, S. K.; Nichols, K. L.; Ahamadeen, N.; Shanahan, M. L.; Rand, K. L. (Frontiers in Pain Research, 2024)
IntroductionDysmenorrhea is associated with increased risk of chronic pain and hyperalgesia. Menstruating individuals with dysmenorrhea are more likely to have elevated pain reactivity when experiencing experimental pain, than those without. However, no study has examined intragroup differences in reactions to experimentally induced pain for individuals with dysmenorrhea. The main aim of this study was to examine the relative roles of dysmenorrhea severity and interference in the experience of experimentally-induced pain.MethodsParticipants were 120 menstruating individuals involved in a larger research study examining the influence of expectations on experimentally-induced pain. As part of the study, participants completed an online questionnaire regarding demographic and menstrual information and participated in a cold pressor task. Participants were randomized into four groups based on the manipulation of two independent variables: (1) high vs. low expectations about pain severity (pain-expectations); (2) and high vs. low expectations about one's pain tolerance (self-expectations). Participants verbally rated their pain severity throughout the cold pressor task using a 0–10 scale. Regression analyses were conducted examining the relationships between dysmenorrhea experience (i.e., average severity and interference) and cold pressor data [pain severity ratings and pain tolerance (i.e., total time in the cold pressor)], controlling for the manipulated expectations and age. Then, moderation analyses were conducted examining expectation group differences.ResultsWhen controlling for manipulated expectations and age, dysmenorrhea severity significantly predicted initial pain severity rating (p = 0.022) but did not predict final pain severity rating (p = 0.263) or pain tolerance (p = 0.120). Dysmenorrhea interference did not predict initial pain severity rating (p = 0.106), final pain severity rating (p = 0.134), or pain tolerance (p = 0.360). A moderation analysis indicated that the relationship between dysmenorrhea severity and initial pain severity rating was not moderated by pain-expectations, χ2(1) = 0.412, p = 0.521.DiscussionDuring an experimentally-induced pain task, dysmenorrhea severity but not interference predicted initial pain severity rating, such that higher levels of dysmenorrhea severity predicted greater initial pain severity rating. This suggests individuals with more severe dysmenorrhea pain may experience greater initial sensitivity to pain and be at risk for increased sensitivity to acute pain and potentially the development of chronic pain.